Transnational migrants' philanthropy: Its forms, operations, and implications from the perspectives of Ghanaian residents in Europe - DeSouza, Mercy; Osei, Onallia Esther; Idemudia, Erhabor Sunday (Frontiers in Sociology, 2023)
Introduction With the emergence of transnational migration studies in the 1990's, migration studies became involved in showing how migrants maintain transnational connections through money and non-monetary philanthropic contributions in their origin countries. However, there is little evidence about the interconnections between different forms of migrants' philanthropy and how they are developed and sustained over time across international borders. Methods This work investigates individual and groups transnational philanthropy and shows how migrants become involved in these forms of philanthropy, highlighting some changes therein over time. We relied on fifty semistructured interviews and six focus group discussions conducted with Ghanaians in the Netherlands, Italy and Germany. Results and discussion Our thematic analyses confirm that transnational migrant philanthropy is about fulfilling certain “moral obligations,” to derive a sense of belonging “here” (destinations) and “there” (origins). In performing the self, religious or culturally imposed sense of responsibility for human welfare and institutional development in the home country, Ghana, involved migrants overcome some challenges. For transnational migrant philanthropy to sustain itself, studied migrants think origin country governments must take necessary steps to remove structural obstacles like tedious procedures for clearing philanthropic goods at the ports and harbors. Involved migrants also suggested a need for a more organized platform to collect relevant information on potential beneficiary needs for their preparations to “give back” to their homeland.